1988
DOI: 10.1177/004051758805800201
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Nylon Ballistic Panels by Fragment-Simulating Projectiles

Abstract: The main purpose of this report is to present an analysis of the ballistic behavior of the fragment-simulating projectile (FSP)-nylon cloth system. For a set of Vc determinations, plots of Vr versus Vs can be adequately represented by hyperbolas. The energy lost by an FSP after complete passage through a nylon ballistic panel of L layers is virtually constant, independent of the striking velocity. The hyperbolas lie on a portion of the surface of a hyperbolic paraboloid with Vr, Vs, and L as axes. The minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 8 publications
3
26
0
Order By: Relevance
“…Prosser [16] analysed fabrics impacted by 0.22 calibre fragment simulating projectiles (FSP) and found that if slippage could be reduced by just four yarns at the impact point, an almost 50% 5 increase in protection could be achieved. Bazhenov [17] reported that in multiple-ply fabric systems, the ravelling of yarns at the unclamped edges is related to the energy transferred to 7 yarns in each fabric layer.…”
Section: Nme1596mentioning
confidence: 99%
“…Prosser [16] analysed fabrics impacted by 0.22 calibre fragment simulating projectiles (FSP) and found that if slippage could be reduced by just four yarns at the impact point, an almost 50% 5 increase in protection could be achieved. Bazhenov [17] reported that in multiple-ply fabric systems, the ravelling of yarns at the unclamped edges is related to the energy transferred to 7 yarns in each fabric layer.…”
Section: Nme1596mentioning
confidence: 99%
“…8. It has been reported that increasing inter-yarn friction improves the ballistic resistance of woven fabrics [12][13][14][15]. With higher friction, it becomes more difficult for a projectile to push yarns apart and hence, they have to engage and break more yarns in order to perforate the fabric.…”
Section: Fabric Deformationmentioning
confidence: 99%
“…The author identified that the work of penetration per interior layer was constant. Penetration mechanisms were described in part II of his work [4], which is focused on providing more evidence that the major mode of failure of the Nylon panels impacted by the FSP were cutting and shearing mechanisms. Ballistic performance of Nylon 6,6 was also compared with the performance of Kevlar 29 in Figucia et al [5].…”
Section: Introductionmentioning
confidence: 99%